1993
DOI: 10.3109/10428199309148211
|View full text |Cite
|
Sign up to set email alerts
|

Chylous Effusion Complicating Chronic Lymphocytic Leukemia

Abstract: We present a case of chylous effusion (CE) occurring in a patient with chronic lymphocytic leukemia (CLL), an observation which has rarely been reported. Therefore, CLL should be added to the differential diagnosis of nontraumatic chylothorax. CE in CLL can be successfully managed by irradiation of the mediastinum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Whether the prognosis for these patients might improve with modern immunochemotherapy remains to be seen. It is also interesting to note that patients with longer reported survival had either successful thoracic duct ligation, mediastinal irradiation or pleurodesis [11,12,17]. In our opinion, this allows for the conclusion that treating physicians should aim for definitive resolution of the chylothorax.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Whether the prognosis for these patients might improve with modern immunochemotherapy remains to be seen. It is also interesting to note that patients with longer reported survival had either successful thoracic duct ligation, mediastinal irradiation or pleurodesis [11,12,17]. In our opinion, this allows for the conclusion that treating physicians should aim for definitive resolution of the chylothorax.…”
Section: Discussionmentioning
confidence: 89%
“…However, mediastinal irradiation can be effective in CLL-associated chylothorax, as demonstrated by Ampil et al , who reported the case of a female CLL patient who developed chylothorax under continuous treatment with chlorambucil and prednisone. Following mediastinal irradiation with 1000 cGy over five days, her chylous effusion resolved during the nearly five years of follow-up [17]. …”
Section: Discussionmentioning
confidence: 99%
“…CLL is a rare cause of chylothorax, and has only been reported in a few other instances. 6-8 Bilateral chylothorax is even rare and has not been frequently reported so far. 9 Usually, the patient with chylothorax remains asymptomatic until a large amount of chyle accumulates in the pleural space.…”
Section: Discussionmentioning
confidence: 99%
“…In another case, the chylothorax was successfully treated with mediastinal irradiation. 6 For our patient, we opted for initial treatment with chemotherapy with the intention to reduce the number of tumor cells and relieve the pseudo obstruction of pleural lymphatics. Currently the patient continues with chest tube drainage on right side and intermittent thoracentesis on left side.…”
Section: Discussionmentioning
confidence: 99%
“…Although such complications have been described in adults with lymphoma and chronic lymphatic leukemia, [1,2] no cases have been reported in children with acute lymphoblastic leukemia (ALL). Our patient, a three-year-old Saudi boy with ALL who developed a malignant chylous pleuropericardial effusion may therefore be instructive.…”
mentioning
confidence: 99%